Role of diet, physical activity and new drugs in the primary management of cancer cachexia in gastrointestinal tumors – a comprehensive review - Oneda, Ester; Manno, Alessandra; Noventa, Silvia; Libertini, Michela; Cherri, Sara; Zaniboni, Alberto (Frontiers in Oncology, 2025)
Cancer cachexia is a multifactorial syndrome characterized by involuntary weight loss, muscle mass reduction, and systemic inflammatory response, negatively impacting the quality of life and survival of cancer patients. In gastrointestinal tumors, cachexia prevalence can reach up to 80%, presenting a complex clinical challenge. This review aims to explore the efficacy of a multimodal approach integrating nutritional support and physical activity in cancer cachexia management. Targeted dietary strategies, such as a high-protein diet enriched with omega-3 and branched-chain amino acids (BCAAs), have proven effective in counteracting muscle loss and modulating inflammatory metabolism. Physical activity, particularly resistance training, contributes to preserving lean mass and improving physical function. However, current data suggest that no single strategy is sufficient to reverse cachexia, necessitating combined treatment with supportive pharmacological therapies, including progestogens, muscle metabolism modulators, and cytokine antagonists. Despite the evidence supporting these interventions, significant gaps remain, highlighting the need for randomized clinical trials to define the optimal therapeutic protocol for gastrointestinal cancer patients with cachexia.